Carboxymethyl cellulose-based aerogel as well as preparation method and application thereof
Through directional refrigeration and ion crosslinking technology, a stable cellulose-based aerogel network structure is formed, which solves the shortcomings of cellulose-based aerogel in terms of structural stability and elasticity, and achieves excellent compression resilience in both air and water, which is suitable for use in pressure sensors and other applications.
Patent Information
- Application Number
- CN202411849864.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing cellulose-based aerogels have shortcomings in structural stability and elasticity, especially in high humidity/underwater environments, which limits their practical application.
By directed freezing of the carboxymethyl cellulose solution to form a layered aerogel matrix and ionic crosslinking is performed in the ethanol solution of iron salt to form a stable network structure, reducing the hydrogen bond between cellulose and improving the elasticity of the aerogel.
It achieves excellent compression elasticity in both air and water, improves the structural stability and elasticity of the aerogel, and is suitable for use in pressure sensors and other applications.
Smart Images

Figure CN119708612A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogel materials, and in particular to an aerogel based on carboxymethyl cellulose and a preparation method and application thereof. Background Art
[0002] Aerogel is a highly dispersed solid material with a porous structure formed by cross-linking colloidal particles or polymer molecules through physical or chemical bonds. It has the advantages of rich pores, large specific surface area, and light weight. It has broad application prospects in many fields such as aerospace, military industry, construction, environmental protection, and flexible devices. Aerogel can be divided into two types according to its composition: inorganic aerogel and organic aerogel. Inorganic aerogel generally has the disadvantages of being fragile and having poor elasticity, and its mechanical properties are difficult to fully meet the requirements of practical applications. Organic aerogel has excellent flexibility and elasticity, and has broader application prospects than inorganic aerogel. However, since its raw materials are mostly petroleum-based compounds such as polyurethane, it does not conform to the strategic direction of sustainable development. Therefore, in the context of the continuous depletion of petrochemical resources and increasingly severe environmental problems, it is of great significance to develop aerogels based on biomass resources.
[0003] Cellulose is the most widely distributed and abundant natural high molecular weight polysaccharide in nature, and cellulose-based aerogels made of cellulose have the advantages of being biodegradable, non-toxic, and renewable, making them an ideal substitute for non-renewable petroleum-based aerogels. However, since dynamic hydrogen bonds are formed between cellulose chains in cellulose-based aerogels, serious structural collapse will occur after the aerogels are deformed, resulting in poor structural stability and insufficient elasticity in the aerogels, which greatly limits the practical application of cellulose-based aerogels. In addition, most existing cellulose-based aerogels are highly hydrophilic, making it difficult to maintain stable performance for a long time in high humidity / underwater environments, and the actual application scenarios are greatly limited.
[0004] Therefore, it is of great significance to develop a cellulose-based aerogel that has excellent compression resilience in both air and water, is non-toxic and environmentally friendly, and conforms to the strategic direction of sustainable development. Summary of the invention
[0005] The purpose of the present invention is to provide an aerogel based on carboxymethyl cellulose and a preparation method and application thereof.
[0006] The technical solution adopted by the present invention is:
[0007] A method for preparing aerogel based on carboxymethyl cellulose comprises the following steps:
[0008] 1) dispersing carboxymethyl cellulose with water to prepare a carboxymethyl cellulose solution, injecting the solution into a mold for directional freezing, and then freeze-drying the solution to obtain a carboxymethyl cellulose aerogel matrix;
[0009] 2) Immersing the carboxymethyl cellulose aerogel matrix in an ethanol solution of an iron salt or an ethanol-water solution of an iron salt for ion crosslinking, and then drying, thereby obtaining an aerogel based on carboxymethyl cellulose.
[0010] Preferably, the mass ratio of the carboxymethyl cellulose in step 1) to the iron salt in step 2) is 1:1-35.
[0011] More preferably, the mass ratio of the carboxymethyl cellulose in step 1) to the iron salt in step 2) is 1:5-15.
[0012] Preferably, the mass fraction of carboxymethyl cellulose in the carboxymethyl cellulose solution in step 1) is 1% to 5%.
[0013] Preferably, the mold cavity of the mold in step 1) is rectangular and is made of polytetrafluoroethylene.
[0014] Preferably, the directional freezing in step 1) is carried out at a temperature of -210°C to -150°C, and the directional freezing time is 0.5h to 1h.
[0015] Preferably, the directional freezing in step 1) comprises the following operation: placing one side of the mold close to a cold source for directional freezing.
[0016] Preferably, the cold source is an iron container filled with liquid nitrogen.
[0017] Preferably, the freeze-drying in step 1) is carried out at a temperature of -60°C to -50°C, and the freeze-drying time is 24h to 72h.
[0018] Preferably, the iron salt in step 2) is at least one of ferric chloride, ferric nitrate and ferric bromide.
[0019] Preferably, the mass fraction of the iron salt in the iron salt ethanol solution in step 2) is 0.5% to 10%.
[0020] Preferably, the mass fraction of the iron salt in the ethanol-water solution of the iron salt in step 2) is 0.5% to 10%, and the mass fraction of ethanol is ≥60% and <99.5%.
[0021] Preferably, the ionic crosslinking in step 2) is carried out at a temperature of 20° C. to 25° C., and the time for the ionic crosslinking is 1 h to 6 h.
[0022] Preferably, the drying method in step 2) is vacuum drying.
[0023] Preferably, the vacuum drying is carried out at a temperature of 20°C to 35°C.
[0024] A carboxymethyl cellulose-based aerogel is prepared by the above preparation method.
[0025] A pressure sensor adopts a pressure sensing material comprising the above-mentioned carboxymethyl cellulose-based aerogel.
[0026] The principle of the present invention is that the carboxymethyl cellulose solution is first directionally frozen, and the layered structure is controlled by ice crystal growth under gradient temperature to form a carboxymethyl cellulose aerogel matrix with a layered and anisotropic structure, and then immersed in an ethanol solution of iron salt or an ethanol-water solution of iron salt (ethanol plays a role in transporting Fe 3+ At the same time, the aerogel morphology is maintained, and the synergistic effect of ethanol and water can improve the permeability of the iron salt solution. 3+ The coordination bonds with the carboxyl groups in the aerogel realize ionic cross-linking to form a stable network structure, reduce the hydrogen bonds between cellulose, and reduce the adhesion between molecules, thereby improving the elasticity of the aerogel, ultimately giving the aerogel high elasticity and enabling the aerogel to have excellent compression resilience in both air and water.
[0027] The beneficial effects of the present invention are as follows: the carboxymethyl cellulose-based aerogel of the present invention has excellent compression resilience in both air and water, its raw material source is abundant, low cost, and easy to obtain, and its preparation method is simple and easy to operate, and is suitable for large-scale industrial production and application.
[0028] Specifically:
[0029] 1) The carboxymethyl cellulose-based aerogel of the present invention is made of carboxymethyl cellulose as the main raw material. Carboxymethyl cellulose has the advantages of abundant sources, low cost, and easy acquisition. The intermolecular interaction between carboxymethyl cellulose molecules can be used to form anisotropic carboxymethyl cellulose aerogels through directional freezing;
[0030] 2) The present invention utilizes ionic crosslinking to 3+ By introducing it into the carboxymethyl cellulose aerogel matrix, a safe and non-toxic aerogel with excellent compression resilience in both air and water was prepared;
[0031] 3) The carboxymethyl cellulose-based aerogel of the present invention has high resilience and excellent compression resilience in both air and water, and is suitable for use in pressure sensors;
[0032] 4) The preparation method of the carboxymethyl cellulose-based aerogel of the present invention is simple and easy to operate, does not require special production equipment, has low production cost, and is suitable for large-scale industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the SEM image of the carboxymethyl cellulose-based aerogel in Example 1.
[0034] Figure 2 This is the SEM image of the carboxymethyl cellulose-based aerogel in Comparative Example 1.
[0035] Figure 3 Graph showing the compression resilience test results of the carboxymethyl cellulose-based aerogels in Example 1 and Comparative Example 1.
[0036] Figure 4 This is a graph showing the compression resilience test results of carboxymethyl cellulose in air environment / underwater environment in Example 1.
[0037] Figure 5 Graph showing the stability test results of the carboxymethyl cellulose-based aerogels in Example 1, Comparative Example 1 and Comparative Example 2 in an underwater environment.
[0038] Figure 6 The actual pictures are of the carboxymethyl cellulose-based aerogels in Example 1 and Comparative Example 4.
[0039] Figure 7 Compression cycle curves of the carboxymethyl cellulose-based aerogels in Example 1, Comparative Example 2 and Comparative Example 3.
[0040] Figure 8 Compression curves of the carboxymethyl cellulose-based aerogels in Examples 1 to 3.
[0041] Fig. 9 This is a graph showing the test results of the sensing performance based on carboxymethyl cellulose in Example 1. DETAILED DESCRIPTION
[0042] The present invention will be further explained and illustrated below in conjunction with specific embodiments.
[0043] Embodiment 1:
[0044] A carboxymethyl cellulose-based aerogel, the preparation method of which is as follows:
[0045] 1) adding 0.1 g of carboxymethyl cellulose to 9.9 g of deionized water, stirring and fully dissolving at 50° C. to prepare a carboxymethyl cellulose solution with a mass fraction of 1%, then injecting the carboxymethyl cellulose solution into a polytetrafluoroethylene mold with a rectangular cavity, and placing one side of the mold close to an iron container filled with liquid nitrogen (cooling temperature range of -210° C. to -196° C.) for directional freezing for 0.5 h, and then placing it in a freeze dryer for freeze drying at -50° C. for 24 h to obtain a carboxymethyl cellulose aerogel matrix;
[0046] 2) The carboxymethyl cellulose aerogel matrix was immersed in an ethanol-water solution of iron salt prepared by 1 g of ferric chloride, 80 g of ethanol and 19 g of deionized water, and immersed at room temperature for 1 hour, and then placed in a vacuum drying oven at 20° C. for 6 hours to obtain a carboxymethyl cellulose-based aerogel (denoted as A1).
[0047] The scanning electron microscope (SEM) image of the carboxymethyl cellulose-based aerogel (A1) in this example is as follows: Figure 1 (Contains SEM images of 3 different magnifications).
[0048] Depend on Figure 1 It can be seen that the carboxymethyl cellulose-based aerogel in this embodiment has a layered structure, and there are obvious cross-links between the layered structures, forming a stable network structure.
[0049] In addition, the carboxymethyl cellulose-based aerogel in this example was immersed in an ethanol-water solution for stability testing. The test found that the layered structure of the aerogel was not damaged, indicating that it has good stability.
[0050] Embodiment 2:
[0051] A carboxymethyl cellulose-based aerogel, the preparation method of which is as follows:
[0052] 1) adding 0.3 g of carboxymethyl cellulose to 9.7 g of deionized water, stirring and fully dissolving at 55° C. to prepare a carboxymethyl cellulose solution with a mass fraction of 3%, then injecting the carboxymethyl cellulose solution into a polytetrafluoroethylene mold with a rectangular cavity, and placing one side of the mold close to an iron container filled with liquid nitrogen (cooling temperature range of -210° C. to -196° C.) for directional freezing for 0.5 h, and then placing it in a freeze dryer for freeze drying at -50° C. for 36 h to obtain a carboxymethyl cellulose aerogel matrix;
[0053] 2) The carboxymethyl cellulose aerogel matrix was immersed in an ethanol-water solution of iron salt prepared by 2 g of ferric chloride, 60 g of ethanol and 38 g of deionized water, and immersed at room temperature for 3 h, and then placed in a vacuum drying oven at 25° C. for 6 h to obtain an aerogel based on carboxymethyl cellulose (denoted as A2).
[0054] Embodiment 3:
[0055] A carboxymethyl cellulose-based aerogel, the preparation method of which is as follows:
[0056] 1) adding 0.5 g of carboxymethyl cellulose to 9.5 g of deionized water, stirring and fully dissolving at 60° C. to prepare a carboxymethyl cellulose solution with a mass fraction of 5%, then injecting the carboxymethyl cellulose solution into a polytetrafluoroethylene mold with a rectangular cavity, and placing one side of the mold close to an iron container filled with liquid nitrogen (cooling temperature range of -210° C. to -196° C.) for directional freezing for 0.5 h, and then placing it in a freeze dryer for freeze drying at -50° C. for 48 h to obtain a carboxymethyl cellulose aerogel matrix;
[0057] 2) The carboxymethyl cellulose aerogel matrix was immersed in an ethanol solution of iron salt prepared by 4 g of ferric chloride and 96 g of ethanol at room temperature for 4 h, and then placed in a vacuum drying oven at 35° C. for 6 h to obtain an aerogel based on carboxymethyl cellulose (denoted as A3).
[0058] Comparative Example 1:
[0059] A carboxymethyl cellulose-based aerogel (without ion crosslinking) is prepared as follows:
[0060] 0.1 g of carboxymethyl cellulose was added to 9.9 g of deionized water, and stirred at 50° C. to fully dissolve to prepare a carboxymethyl cellulose solution with a mass fraction of 1%. The carboxymethyl cellulose solution was then injected into a polytetrafluoroethylene mold with a rectangular cavity, and one side of the mold was placed close to an iron container filled with liquid nitrogen (cooling temperature range of -210° C. to -196° C.) for directional freezing for 0.5 h, and then placed in a freeze dryer for freeze drying at -50° C. for 24 h to obtain a carboxymethyl cellulose-based aerogel (denoted as B1; the same as the carboxymethyl cellulose aerogel matrix in Example 1).
[0061] The SEM image of the carboxymethyl cellulose-based aerogel (B1) in this comparative example is as follows: Figure 2 (Contains SEM images of 3 different magnifications).
[0062] Depend on Figure 2 It can be seen that the carboxymethyl cellulose-based aerogel in the comparative example has a very regular layered structure, but the cross-linking density between the layered structures is low, indicating that the directional freezing process can form a carboxymethyl cellulose aerogel matrix with a layered structure, and ionic cross-linking can further form a stable network structure.
[0063] Comparative Example 2:
[0064] A carboxymethyl cellulose-based aerogel (without iron salt added), the preparation method of which is as follows:
[0065] The carboxymethyl cellulose aerogel matrix (same as in Example 1) was immersed in an ethanol aqueous solution prepared by 80 g of ethanol and 20 g of deionized water, immersed at room temperature for 1 hour, and then placed in a vacuum drying oven at 20° C. for 6 hours to obtain a carboxymethyl cellulose-based aerogel (denoted as B2).
[0066] Comparative Example 3:
[0067] A carboxymethyl cellulose-based aerogel (frozen in a refrigerator) is prepared as follows:
[0068] 1) adding 0.1 g of carboxymethyl cellulose to 9.9 g of deionized water, stirring and fully dissolving at 50° C. to prepare a carboxymethyl cellulose solution with a mass fraction of 1%, injecting the carboxymethyl cellulose solution into a polytetrafluoroethylene mold with a rectangular cavity, and placing the mold in a refrigerator (at a temperature of about -21° C.) for 24 hours, and then placing it in a freeze dryer for freeze drying at -50° C. for 24 hours to obtain a carboxymethyl cellulose aerogel matrix;
[0069] 2) The carboxymethyl cellulose aerogel matrix was immersed in an ethanol-water solution of iron salt prepared by 1 g of ferric chloride, 80 g of ethanol and 19 g of deionized water, and immersed at room temperature for 1 hour, and then placed in a vacuum drying oven at 20°C for 6 hours to obtain a carboxymethyl cellulose-based aerogel (denoted as B3).
[0070] Comparative Example 4:
[0071] A carboxymethyl cellulose-based aerogel (without ethanol addition), the preparation method of which is as follows:
[0072] The carboxymethyl cellulose aerogel matrix (same as in Example 1) was immersed in an iron salt aqueous solution prepared by 1 g of ferric chloride and 99 g of deionized water, immersed at room temperature for 1 hour, and then placed in a vacuum drying oven at 20° C. for 6 hours to obtain a carboxymethyl cellulose-based aerogel (denoted as B4).
[0073] Aerogel compression performance, underwater stability and sensing performance testing:
[0074] 1) The carboxymethyl cellulose-based aerogels in Example 1 and Comparative Example 1 (respectively CMC / Fe 3+ aerogel and CMC aerogel; the sample is in the shape of a cuboid, with a size of 30mm×25mm×10mm) and is placed on the experimental table. It is pressed along the thickness direction until the deformation degree ε reaches 50%, and then the pressure is removed. When the sample thickness remains stable, the deformation degree of the sample is tested. The compression resilience test results of the aerogel are as follows: Figure 3(a is the carboxymethyl cellulose-based aerogel in Comparative Example 1, and b is the carboxymethyl cellulose-based aerogel in Example 1).
[0075] Depend on Figure 3 It can be seen that the carboxymethyl cellulose-based aerogel in Comparative Example 1 cannot recover to its original thickness after compression, while the carboxymethyl cellulose-based aerogel in Example 1 can recover to its original thickness and has excellent compression resilience.
[0076] 2) The carboxymethyl cellulose-based aerogel in Example 1 (the sample is in the shape of a cuboid, with a size of 30 mm×25 mm×10 mm) is placed in an air environment / underwater environment, and pressed along the length direction until the deformation degree ε reaches 70%. The pressure is then removed, and the deformation degree of the sample is tested after the length of the sample remains stable. The compression resilience test results of the aerogel in the air environment / underwater environment are as follows: Figure 4 shown.
[0077] Depend on Figure 4 It can be seen that the carboxymethyl cellulose-based aerogel in Example 1 can recover to its original length after being compressed in an air environment / underwater environment, and has excellent compression resilience.
[0078] 3) The carboxymethyl cellulose-based aerogels in Example 1, Comparative Example 1 and Comparative Example 2 were immersed in deionized water for 72 hours respectively, and the dissolution of the aerogels was observed. The stability test results of the obtained aerogels in an underwater environment are as follows: Figure 5 (The samples in each small figure in the figure are Comparative Example 1, Comparative Example 2 and Example 1 from left to right, marked as a, b and c).
[0079] Depend on Figure 5 It can be seen that the carboxymethyl cellulose-based aerogels in Comparative Examples 1 and 2 are completely dissolved after being immersed in an underwater environment for 2 hours, while the carboxymethyl cellulose-based aerogel in Example 1 does not undergo obvious dissolution after being immersed in an underwater environment for 72 hours, and has excellent underwater stability.
[0080] 4) The physical pictures of the aerogel based on carboxymethyl cellulose in Example 1 and Comparative Example 4 are as follows: Figure 6 (The upper part of the figure is the surface view, and the lower part is the cross-sectional view).
[0081] Depend on Figure 6It can be seen that since ethanol was not used in Comparative Example 4, large pores were generated inside the obtained aerogel and the original layered structure was destroyed. The reason is that the carboxymethyl cellulose aerogel that has not been ionically cross-linked will dissolve in water. When immersed in an iron salt aqueous solution, the outer layer will be cross-linked and hardened, while the inner layer will dissolve the carboxymethyl cellulose molecules due to the rapid penetration of water molecules, and the structure will be destroyed. In Example 1, ethanol was added, and the internal layered structure of the obtained aerogel remained intact and elastic.
[0082] 5) The carboxymethyl cellulose-based aerogels in Example 1, Comparative Example 2 and Comparative Example 3 (the samples were in the shape of rectangular parallelepipeds with a size of 30 mm×25 mm×10 mm) were placed on a compression plate, and then a compression test was performed using a universal tensile testing machine (KYD-2000NS, China) with a compression rate set to 20 mm / min. The compression cycle curves of the obtained aerogels are shown in FIG. Figure 7 (a is comparative example 2, b is comparative example 3, and c is embodiment 1).
[0083] Depend on Figure 7 It can be seen that the compression curve of the carboxymethyl cellulose-based aerogel (without adding iron salt) in Comparative Example 2 has a very large hysteresis, and its stress quickly becomes 0 after unloading, indicating that the aerogel cannot recover in time after the external force is removed, and the compression resilience is very poor; the carboxymethyl cellulose-based aerogel in Comparative Example 3 (frozen in a refrigerator) does not immediately become 0 after the external force is unloaded, indicating that the aerogel has a certain compression resilience, but from the hysteresis area in its compression curve, its compression resilience is still not good enough; the hysteresis area in the compression curve of the carboxymethyl cellulose-based aerogel in Example 1 is the smallest, and the stress gradually decreases to 0 during the unloading process, indicating that the aerogel has very excellent compression resilience.
[0084] 6) The carboxymethyl cellulose-based aerogels in Examples 1 to 3 (the samples were in the shape of rectangular parallelepipeds with sizes of 30 mm×25 mm×10 mm) were placed on a compression plate, and then a compression test was performed using a universal tensile testing machine (KYD-2000NS, China) with a compression rate set to 20 mm / min. The compression curve of the obtained aerogels is shown in FIG. Figure 8 shown.
[0085] Depend on Figure 8It can be seen that the ethanol content in the iron salt solution has a significant impact on the compression properties of the aerogel. As the ethanol content increases from 60% (A2) to 80% (A1), the compression rebound performance of the aerogel increases. The reason is that too high water content in the iron salt solution will enhance the movement of carboxymethyl cellulose in the system, which is not conducive to the maintenance of the layered structure. When the iron salt solution is completely free of water (A3), due to the flocculation effect of ethanol on the carboxymethyl cellulose molecules, the iron salt solution will not be easily dispersed in the aerogel, which is not conducive to the cross-linking. Therefore, the elasticity will be reduced.
[0086] 7) The carboxymethyl cellulose-based aerogel in Example 1 (the sample is in the shape of a cuboid, with a size of 30 mm×25 mm×10 mm) is sandwiched between two copper foils to assemble into pressure sensor A and pressure sensor B. Then, in an air environment, pressure sensor A is attached to the wrist of the tester, and the wrist is repeatedly bent and straightened. In an underwater environment, pressure sensor B is attached to the finger joints of the tester, and the finger joints are repeatedly bent and straightened. A desktop digital multimeter (VC8165, China) is then used to record the real-time resistance change of the aerogel in the air environment / underwater environment. The sensing performance test results of the obtained aerogel are as follows: Fig. 9 (a is the air environment, b is the underwater environment).
[0087] Depend on Fig. 9 It can be seen that the pressure sensor assembled from the carboxymethyl cellulose-based aerogel in Example 1 can effectively monitor the activities of human body parts such as wrists and fingers in air environments / underwater environments, indicating that the carboxymethyl cellulose-based aerogel of the present invention is suitable as a pressure sensing material for pressure sensors.
[0088] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing aerogel based on carboxymethyl cellulose, characterized in that: The following steps are involved: 1) dispersing carboxymethyl cellulose with water to prepare a carboxymethyl cellulose solution, injecting the solution into a mold for directional freezing, and then freeze-drying the solution to obtain a carboxymethyl cellulose aerogel matrix; 2) Immersing the carboxymethyl cellulose aerogel matrix in an ethanol solution of an iron salt or an ethanol-water solution of an iron salt for ion crosslinking, and then drying, thereby obtaining an aerogel based on carboxymethyl cellulose.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the carboxymethyl cellulose in step 1) to the iron salt in step 2) is 1:1-35.
3. The preparation method according to claim 1, characterized in that: Step 1) The mass fraction of carboxymethyl cellulose in the carboxymethyl cellulose solution is 1% to 5%.
4. The preparation method according to any one of claims 1 to 3, characterized in that: Step 1) The directional freezing is carried out at a temperature of -210°C to -150°C, and the directional freezing time is 0.5h to 1h.
5. The preparation method according to any one of claims 1 to 3, characterized in that: Step 1) The freeze drying is carried out at a temperature of -60°C to -50°C, and the freeze drying time is 24h to 72h.
6. The preparation method according to claim 1, characterized in that: The mass fraction of the iron salt in the ethanol solution of the iron salt in step 2) is 0.5% to 10%; the mass fraction of the iron salt in the ethanol-water solution of the iron salt in step 2) is 0.5% to 10%, and the mass fraction of ethanol is ≥60% and <99.5%.
7. The preparation method according to any one of claims 1 to 3 and 6, characterized in that: Step 2) The ionic crosslinking is carried out at a temperature of 20° C. to 25° C., and the time of the ionic crosslinking is 1 h to 6 h.
8. The preparation method according to any one of claims 1 to 3 and 6, characterized in that: The drying method in step 2) is vacuum drying.
9. An aerogel based on carboxymethyl cellulose, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8.
10. A pressure sensor, characterized in that: The pressure sensing material used comprises the carboxymethyl cellulose-based aerogel as claimed in claim 9.
Citation Information
Patent Citations
Preparation method of stimuli-responsive hydrogel
CN115181383A
Polysaccharide-based multi-network gradient structure physical self-lubricating hydrogel as well as preparation method and application thereof
CN116731348A
Biomass modified polyacrylamide conductive hydrogel flexible sensing material and preparation method thereof
CN118271652A